KINERJA BADAN PERMUSYAWARATAN DESA (BPD) DALAM OTONOMI DESA - Haris, Abdul (PERSPEKTIF, 2016)
This study aims to determine the performance of BPD, and to investigate any obstacles encountered BPD in carrying out its duties and functions. This research was conducted in Wonosari. The method used in this research is descriptive qualitative approach. The survey results revealed that the BPD has been able to carry out the functions and duties, but not optimal, due to lack of good knowledge of the BPD regarding their duties and functions, the financial problems of BPD and its members, as well as the lack of participation from the community caused by a lack of socialization.